Pengaruh DER, firm size, NPM, EPS, ROE, dan EVA terhadap nilai perusahaan pada perusahaan sektor properti dan real estate yang terdaftar di BEI periode 2011-2015 - Juwita, Karina (Universitas Tarumanagara, 2017)
This study aimed to determine the effect of Debt Equity Ratio (DER), Firm Size, Net Profit Margin (NPM), Earning per Share (EPS), Return on Equity (ROE), and Economic Value Added (EVA) on Price Book Value (PBV). This study is still conducted regards different results of various research. The research was conducted using secondary data. The population in this study are all property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the year 2011-2015. The sampling method applies the purposive sampling technique. The data analysis uses data panel regression analysis. The results of the regression analysis showed that the Debt Equity Ratio and Earning per Share do not affect Price Book Value (PBV). Firm Size, Net Profit Margin, and Economic Value Added have negative effects and are significant on Price Book Value (PBV), while the Return on Equity positively affects and is significant on Price Book Value (PBV). The adjusted R-squared value is 0.3043. These results indicate that the variable ability of Debt Equity Ratio (DER), Firm Size, Net Profit Margin (NPM), Earning per Share (EPS), Return on Equity (ROE), and Economic Value Added (EVA) to explain Price Book Value is 30.43% while the remaining 69.57% is explained by other variables.